Factors Associated With Accuracy of Self-Assessment Compared With Tested Non-English Language Proficiency Among Primary Care Providers - Diamond, Lisa; Toro Bejarano, Marcela; Chung, Sukyung; Ferguson, Warren; Gonzalez, Javier; Genoff Garzon, Margaux; Mujawar, Imran; Gany, Francesca (Medical care, 2019)
There are no accepted best practices for clinicians to report their non-English language (NEL) fluencies. Language discordance between patients with limited English proficiency and their clinicians may contribute to suboptimal quality of care. To compare self-assessed clinician NEL proficiency with a validated oral language proficiency test. To identify clinician characteristics associated with self-assessment accuracy. Primary care providers from California and Massachusetts. We surveyed 98 clinicians about demographics and their NEL self-assessment using an adapted version of the Interagency Language Roundtable (ILR) scale followed by an oral proficiency interview: The Clinician Cultural and Linguistic Assessment (CCLA). We compared the ILR to the CCLA and analyzed factors associated with the accuracy of self-assessment. Ninety-eight primary care providers participated: 75.5% were women, 62.2% were white, and Spanish was the most common NEL reported (81.6%). The average CCLA score was 78/100 with a 70% passing-rate. There was a moderate correlation between the ILR and CCLA (0.512; P<0.0001). Participants whose self-reported levels were "fair" and "poor" had a 0% pass-rate and 100% who self-reported "excellent" passed the CCLA. Middle ILR levels showed a wider variance. Clinicians who reported a NEL other than Spanish and whose first language was not English were more likely to accurately self-assess their abilities. Self-assessment showed a moderate correlation with the validated CCLA test. Additional testing may be required for clinicians at the middle levels. Clinicians whose native languages were not English and those using languages other than Spanish with patients may be more accurate in their self-assessment.